Modulation of LPS-induced RAW 264.7 macrophages by Pulsatilla koreana-synthesized gold nanoparticles - Han, Yaxi; Zhang, Xindi; Zhu, Ling; Wang, Kunlun; Sha, Dixin; Ji, Nina; Fan, Jing; Chen, Qing; Chen, Kaixin; Zhou, Ye; Yao, Xinmiao; Li, Bo; et al. (Frontiers in Nutrition, 2025)
Biosynthesis of gold nanoparticles using medicinal plants has emerged as a promising strategy in nanobiotechnology due to their distinctive therapeutic attributes, including biological specificity, low cytotoxicity, and inherent biocompatibility. This study presents a straightforward phytosynthetic approach that eliminates requirements for additional stabilizing agents, demonstrating exceptional process simplicity and efficiency. The formation of Pk-AuNps was confirmed by UV–Vis spectroscopy with maximum absorbance at 540 nm. Comprehensive characterization through FE-TEM, EDX, and XRD revealed spherical morphology with face-centered cubic crystalline structure, while FTIR identified critical functional groups responsible for biological activity of Pk-AuNps. DPPH radical scavenging, ABTS inhibition, and ferric reducing power analysis further revealed that Pk-AuNps possess strong antioxidant activity. Cytocompatibility evaluations in RAW264.7 and A549 cell lines revealed excellent biosafety characteristics of Pk-AuNps, highlighting their biocompatibility for potential biomedical applications. Furthermore, the anti-inflammatory properties of Pk-AuNps in LPS-stimulated murine macrophages were also investigated. Notably, Pk-AuNps demonstrated potent anti-inflammatory effects in LPS-activated macrophages, significantly attenuating pro-inflammatory mediators through dual mechanisms: (1) Inhibition of NO and PGE2 production, and (2) Downregulation of iNOS and COX-2 gene expression. These findings indicate that Pk-AuNps show promise as functional food ingredients, demonstrating multifunctional bioactive properties to developing anti-inflammatory nutraceuticals.